A unique glycan-isoform of transferrin in cerebrospinal fluid: A potential diagnostic marker for neurological diseases - Hoshi, Kyoka; Matsumoto, Yuka; Ito, Hiromi; Saito, Kiyoshi; Honda, Takashi; Yamaguchi, Yoshiki; Hashimoto, Yasuhiro (Biochimica et biophysica acta. General subjects, 2017)
Cerebrospinal fluid (CSF) is sequestered from blood by the blood-brain barrier and directly communicates with brain parenchymal interstitial fluid, leading to contain specific biomarkers of neurological diseases. CSF contains glycan isoforms of transferrin (Tf): one appears to be derived from the brain and the other from blood. CSF contains two glycan-isoforms; brain-type Tf and serum-type Tf. Glycan analysis and immunohistochemistry suggest that serum-type Tf having α2, 6sialylated glycans is derived from blood whereas brain-type Tf having GlcNAc-terminated glycans is derived from the choroid plexus, CSF producing tissue. The ratio of serum-type/brain-type Tf differentiates Alzheimer's disease from idiopathic normal pressure hydrocephalus, which is an elderly dementia caused by abnormal metabolism of CSF. The ratios in Parkinson's disease (PD) patients were higher than those of controls and did not appear to be normally distributed. Indeed, detrended normal Quantile-Quantile plot analysis reveals the presence of an independent subgroup showing higher ratios in PD patients. The subgroup of PD shows higher levels of CSF α-synuclein than the rest, indicating that PD includes two subgroups, which differ in levels of brain-type Tf and α-synuclein. Glycosylation in central nervous system appears to be unique. The unique glycan may be a tag for glycoprotein, which is biosynthesized in the central nervous system. This article is part of a Special Issue entitled Neuro-glycoscience, edited by Kenji Kadomatsu and Hiroshi Kitagawa. [Display omitted] •Cerebrospinal fluid contains two glycan isoforms of transferrin.•One isoform appears to be produced in the brain and another is derived from serum.•The isoform produced in the brain is a marker for neurological diseases.